Prevalence of posttraumatic stress disorder and associated disorders among adolescents in public schools: a crosssectional study - ASTITENE, KHALID; BARKAT, AMINA (International Journal of Psychosocial Rehabilitation, 2024)
Anyone can develop post-traumatic stress disorder (PTSD) following a traumatic event; this disorder can develop comorbid PTSD disorders such as anxiety and depression which could seriously interfere with the daily life of the adolescent who was be the subject of our study by evaluating the prevalence of PTSD in public schools and also evaluating the impact of this disorder. Among 94 schools, 10 high schools and 15 middle schools were selected. 1250 students were selected for a cross-sectional survey with an age of 12 to 17 years (14.98 ± 1.49). The survey was carried out during the period from March to June 2017. Standardized questionnaires (Life Events Checklist, CPTS-RI, STAIY and CDI) were used. A high prevalence of PTSD was found with 44.4% which is explained by the inclusion of the date of event from 1 month to 3 months and the specificity of a population of Moroccan schoolchildren (lack of social support, parental illiteracy, poverty, precariousness, unemployment) with 62% of PTSD in girls versus 38% in boys (p <0.001). Among adolescents in school with PTSD, anxiety was 78.81% and depression was 51.7% with a dominance of girls (p <0.001 for both disorders). We had found 73% of students who had declining academic results and 5.8% of adolescents had thought about suicide. Post-traumatic stress disorder has a negative impact on the well-being of adolescents, which is why it is necessary to adapt suitable treatments immediately after a traumatic event or during the disease.